P845 Deep vein thrombosis, pulmonary embolism and patent foramen ovale: a lethal mix. (17th January 2020) - Vera Sainz, A; Garcia Guimaraes, M; Jimenez, C; De La Cuerda, F; Gonzalez, E; Montes, A; De Rueda, C; Rojas, A; Cecconi, A; Diego, G; Benedicto, A; Dominguez, L; et al.
Abstract: A 50-year-old woman without remarkable medical history was admitted at the Emergency Department for acute dyspnoea. The patient had been recently submitted to C5-C6 microdiscectomy. She was tachypneic and oxygen saturation was 88%. CT angiography showed bilateral pulmonary embolism (PE) (Figure 1A, yellow arrowheads) with signs of right ventricle overload. Bilateral deep vein thrombosis was also confirmed. The patient was admitted at the Intensive Care Unit, clinically stable. Few hours later, she presented sudden hemodynamic and respiratory deterioration, requiring invasive mechanical ventilation and vasopressors. Due to recent cervical surgery, systemic fibrinolysis was ruled out. Decision for percutaneous thrombectomy and inferior vena cava filter placement was made. Nevertheless, percutaneous thrombectomy was unsuccessful due to the impossibility to catheterize pulmonary artery. Contrast injection demonstrated that the guiding catheter was located in the left atrium (Figure 1B), suggesting a patent foramen ovale (PFO). Transoesophageal echocardiogram confirmed the presence of a 5x6 mm PFO with right-to-left shunt (Figures 1C – yellow arrows, and 1D). In addition, a 4 cm mobile mass attached to the aortic valve and protruding throughout the left ventricle outflow tract was visualized, suggesting paradoxical embolism (Figure 1E – white arrows). Accordingly, open surgical approach with pulmonary thrombectomy, PFO closure and removal of the left-sided thrombus was decided. Unfortunately, despite careful cannulation, thrombus was not found when aortic valve was inspected. Worst suspicions were confirmed, when the patient presented non-reactive mydriatic pupils. A brain CT showed signs of an extensive bihemisferic ischemic stroke (Figure 1F) presumably related to cerebral embolization of aortic thrombus. The patient finally died. Autopsy study was not consented. PFO has been associated with paradoxical embolisms and risk of stroke in PE. This case strikingly illustrates that treatment of these patients may be challenging in spite of an adequate diagnosis and management.